CAMPUR KODE SEBAGAI STRATEGI KOMUNIKASI DALAM PEMBELAJARAN BAHASA INDONESIA - Em Fathir, Reval; Tryvia, Zeira; Syalsa Ramadani, Putri; Deswina, Dea; Refany, Regita; Olva Zuve, Farel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Code-mixing is a linguistic phenomenon that frequently occurs in Indonesian language learning, particularly in multilingual classroom contexts influenced by technological development and popular culture. This article aims to examine code-mixing as a communication strategy used by teachers and students in Indonesian language instruction. The study employs a qualitative descriptive approach, with data collected through classroom observations, recordings of instructional interactions, and analysis of spoken utterances. The findings indicate that code-mixing is consciously used to clarify meaning, enhance comprehension of learning materials, build emotional closeness, and create a more communicative and interactive learning atmosphere. In addition, code-mixing functions as a linguistic bridge for students who come from diverse first-language backgrounds. However, the use of code-mixing needs to be carefully managed so that it does not hinder the mastery of Indonesian as the target language of instruction. Therefore, code-mixing can be regarded as an effective communication strategy when applied proportionally and in accordance with instructional objectives. This article is expected to contribute both theoretically and practically to the development of Indonesian language teaching strategies that are adaptive to students’ linguistic realities.